Dampak Tata Kelola Perusahaan, Energi Terbarukan, dan Pengelolaan Limbah terhadap Sustainable Development Goals (SDGs) - Kurnia Putri, Pradita Andina; Sunarti, Sunarti; Rochmah, Annisa Nur; Jannah, Maufirotul; Pandin, Maria Yovita R. (Universitas Katolik Widya Karya Malang, 2025)
This study aims to analyze the impact of corporate governance, renewable energy, and waste management on sustainable development goals (SDGs) at PT Rajawali Dwi Putra Indonesia. The three variables were chosen because they are closely related to sustainability activities that have become a global focus, especially in facing environmental, economic, and social challenges. This study uses a quantitative approach with data collection techniques through a 1-5 Likert scale questionnaire distributed to all company employees through the census method. Data analysis was conducted using multiple linear regression which includes validity, reliability, classical assumptions, and hypothesis testing (t test and F test). The results showed that partially, renewable energy and corporate governance have a significant positive effect on development goals. Meanwhile, waste management also has a significant effect yet a negative relationship direction. Simultaneously, the three independent variables have a significant positive effect on sustainable development goals. These findings are expected to be a reference for companies in formulating sustainability strategies and supporting the acceleration of achieving sustainable development goals, especially in developing countries such as Indonesia.